Political football regulation, globalization, and the market - Grant, Wyn 1947- (Agenda Publishing, 2023)
Football has been largely exempt from the development of the regulatory state and has been left to govern itself. However, new media have raised the profile of the game and globalization has created new pressures as football clubs become pawns in the ambitions of states, consortia and wealthy individuals. Clubs offer an important sense of identity for fans, but the impersonality and distance of ownership can set up new tensions. In addition, corruption in the international governing body has been a significant problem and the sport's symbiotic relationship with gambling continues to be a concern. Wyn Grant examines the political economy of football and its uneasy relationship with the market. There are no off-the-shelf solutions for regulation, he argues, but the complexities of the game and its economic size demand more attention from government
Title from publisher's bibliographic system (viewed on 08 Jan 2024)
Keywords: Soccer / Political aspects; Soccer / Economic aspects; Fußball; Sportpolitik; Politische Ökonomie